2021
DOI: 10.3390/nu13020376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Protein-Rich, Low-Glycaemic Meal Replacement on Changes in Dietary Intake and Body Weight Following a Weight-Management Intervention—The ACOORH Trial

Abstract: Although meal replacement can lead to weight reduction, there is uncertainty whether this dietary approach implemented into a lifestyle programme can improve long-term dietary intake. In this subanalysis of the Almased Concept against Overweight and Obesity and Related Health Risk (ACOORH) study (n = 463), participants with metabolic risk factors were randomly assigned to either a meal replacement-based lifestyle intervention group (INT) or a lifestyle intervention control group (CON). This subanalysis relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…The ACOORH study is an international, multicentre randomised-controlled trial analysing the effect of a meal-replacement based lifestyle intervention in overweight or obese persons with components of the metabolic syndrome. Details had been published before [15][16][17][18][19]. In brief, individuals aged 21-65 years, with a body mass index (BMI) of 27-35 kg/m 2 and/or a waist circumference of ≥88 (females) or ≥102 cm (males) and fulfilling at least one of the following criteria of the metabolic syndrome: (a) fasting blood glucose (FBG) 100-125 mg/dL, (b) triglycerides 150-400 mg/dL, (c) high-density lipoprotein (HDL)-cholesterol < 40 mg/dL, or (d) untreated systolic blood pressure of 140-160 mmHg or diastolic blood pressure of 90-100 mmHg or anti-hypertensive medication were eligible for participation.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACOORH study is an international, multicentre randomised-controlled trial analysing the effect of a meal-replacement based lifestyle intervention in overweight or obese persons with components of the metabolic syndrome. Details had been published before [15][16][17][18][19]. In brief, individuals aged 21-65 years, with a body mass index (BMI) of 27-35 kg/m 2 and/or a waist circumference of ≥88 (females) or ≥102 cm (males) and fulfilling at least one of the following criteria of the metabolic syndrome: (a) fasting blood glucose (FBG) 100-125 mg/dL, (b) triglycerides 150-400 mg/dL, (c) high-density lipoprotein (HDL)-cholesterol < 40 mg/dL, or (d) untreated systolic blood pressure of 140-160 mmHg or diastolic blood pressure of 90-100 mmHg or anti-hypertensive medication were eligible for participation.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…During all study visits, anthropometrical data (BMI, body weight, fat mass, lean body mass) were measured and blood was collected as described before [15][16][17][18][19]. Leptin, fasting insulin, interleukin (IL)-6, and C-reactive protein (CRP) were analysed in an accredited medical laboratory (Synlab, Leinfelden, Germany) according to previous reports [20,21] and ratios for leptin/body weight, leptin/fat mass, insulin/body weight, and insulin/fat mass were calculated.…”
Section: Outcomes and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted this was a small-scale study and caution should be exercised when interpreting these findings. However, further research on VLCD and meal replacement products is warranted, especially as an increasing number of meal replacement products are available and some have been evaluated in depth in weight loss studies focusing upon body composition, metabolic, and inflammatory measures [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Protein-rich Foods and Preservation Of Ffmmentioning
confidence: 99%
“…The multicenter, international and randomized controlled ‘Almased Concept against Overweight and Obesity and Related Health Risk’ (ACOORH)-trial was initiated to investigate the additional effect of a low-carbohydrate formula diet on top of a low-intensity lifestyle intervention in comparison to a lifestyle intervention alone in a larger cohort of high-risk individuals with overweight or obesity and at least one further co-morbidity of the metabolic syndrome. Previously published works of the ACOORH trial have already shown a beneficial effect on the prediabetes conversion rate to normoglycemia [ 12 ], weight loss [ 13 ] and nutritional behavior [ 14 ], as well as glucometabolic and inflammatory markers [ 15 ]. The present study analyzed the changes in hemodynamic parameters after 6 and 12 months.…”
Section: Introductionmentioning
confidence: 99%